Organizational routines and context alteration: a reconciliation - Stańczyk-Hugiet, Ewa; Piórkowska, Katarzyna; Stańczyk, Sylwia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The ability to adapt to a changing environment is necessary for the survival of organizations. The choice under uncertainty conditions is one of the central problems in managerial theories of choice. That is also the reason why evolutionary researchers seek a way of adapting to the environment, and one of the concepts embedded in an evolutionary stream are the routines. The routines constitute a generative, dynamic, and emerging system that creates various effects regarded as the continuum: from very stable to continuously changeable ones. The purpose of the paper is to shed light on the routine concept based on the management, evolutionary and change literature. Consequently the paper presents a conceptual framework concerning the relationships between the relative rate of the context changes and the nature of routines, resulting in their different types. The potential setting and research directions for the empirical studies based on this conceptual framework have been also addressed. The methodology encompasses a deductive approach and the method that has been used is critical literature studies. The overarching key finding of the paper is that routines constitute a social phenomenon that is always a barrier to changes, yet regarding evolutionary theory, it is also the chance for changes
Argumenta Oeconomica, 2017, Nr 2 (39), s. 341-372
Keywords: organizational evolution and change; organizational routines; evolutionary approach